Acute and Sub-Acute Toxicity Assessment of the Hydroalcoholic Extract of Madhuca Longifolia Leaves in Wistar Rats. Issue 3 (3rd July 2019) - Devi, N.; Sangeetha, R.
ABSTRACT: The in vivo acute and sub-acute toxicity of the hydroalcoholic leaf extract of Madhuca longifolia (HAEML) were evaluated as per the OECD guidelines. In the acute toxicity study, Albino Wistar rats were administered orally with 2000 mg kg −1 b.w. of HAEML and the animal behavior, adverse effect and mortality were observed for 14 d. Sub- acute toxicity study was conducted by oral administration of the extracts at daily doses of 200 and 400 mg kg −1 b.w. for 28 d. At the end of the treatment period the rats were sacrificed for hematological, biochemical and histopathological studies. No toxic signs or mortality were observed during the experimental period. Hence, the LD50 of the HAEML extracts was determined to be greater than 2000 mg kg −1 b.w. In repeated dose sub-acute toxicity study, the results did not reveal any treatment-related abnormalities in terms of body weight, relative organ weight and biochemical parameters. However, there was a notable difference in hematological profile and antioxidant enzymes. No gross morphological alteration was observed in histopathological studies.